Walking the line? An investigation into elite athletes' sport-related use of painkillers and their willingness to use analgesics to train or compete when injured. (December 2021) - Overbye, Marie
Pain and injuries are inevitable occupational hazards and health risks in athletes' working lives. The sport-related use of analgesics with and without injury is widespread. Taking analgesics to compete while injured is conceptualised as a sickness presenteeism problem. This study examines the complexity of the sport-related use of analgesics in elite sport. A mixed-method design was adopted consisting of a survey ( n =775) and interviews ( n =21) with elite athletes. Many athletes reported a sport-related use of analgesics. Analgesics had commonly been used to enable an injured athlete to: compete in an important match; train during an important period; qualify for an important match/final; and keep one's position on the team or have one's contract prolonged. In particular, team-sport athletes had experience of such use. Apart from the therapeutic use of analgesics, they were sometimes integrated into different routines: for example, enhancing performance, avoid lowering performance, aiding recovery, training/competing injured and prophylactic use. Simultaneously, many had refrained from using or sought to minimise their sport-related use of analgesics; reasons were related to: trust in/feeling the body, side-effects, knowledge and social norms. Social norms and interaction with support personnel played a key role. Physiotherapists and doctors often advised athletes on analgesics, but self-administered use was widespread. How risk cultures manifested themselves varied greatly between sports, and gender differences were scarce. Although 'absenteeism' is also present, a majority of athletes would be willing to 'walk the line', using analgesics to compete when injuries may threaten their career or sporting success.